The Effects of Tourism Product , Service Quality, and Health Protocol to Satisfaction and Revisit Intention of Tourist in Three Gilis West Nusa Tenggara - Muhammad Yusuf Alwi; Abdul Rahman Kadir; Abdul Razak Munir (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2022)
This study aims to analyze the influence of tourism product, service quality, and health protocol on tourist satisfaction and revisit intention, this research was done in three gilis west Nusa Tenggara which are gili trawangan, gili air, and gili meno and there were 388 respondents have been set in this research. the analysis technique used was structural equation modeling (SEM). the result of this research showed that tourism product has a positive and significant influence on tourists’ satisfaction and revisit intention, service quality has a positive and significant influence on tourists’ satisfaction and revisit intention, on the other health protocol has positive but no significant influence on tourists’ satisfaction and revisit intention. tourists’ satisfaction has a positive and significant influence on tourists’ visits.